Performance analysis of the mechanical vapor compression desalination system driven by an organic Rankine cycle. (15th December 2017) - He, W.F.; Ji, C.; Han, D.; Wu, Y.K.; Huang, L.; Zhang, X.K.
Abstract: A desalination system through mechanical vapor compression (MVC), coupling with an organic Rankine cycle (ORC) to drive the steam compressor, is proposed in this paper. Integrated mechanisms of the coupled desalination system are simulated and demonstrated based on the first and second law of thermodynamics, and the corresponding thermal performance is analyzed. Based on the system characteristics at the designed conditions for five types of working fluid, top temperature at the outlet of the boiler and the ambient temperature are designated to illustrate the evocable influence principles. It is observed that the variation trend of the performance both for the ORC and MVC is similar, and the maximum values of the freshwater production and gained output ratio (GOR) are acquired, which are very close for all types of the prescribed working fluid, with m w = 1.09 kgs -1 and GOR = 3.15 for the case of R245fa. Moreover, it is also obtained that a higher top temperature and a lower ambient temperature are beneficial both for the freshwater production and energy conversion efficiency. Highlights: The MVC desalination system driven by an ORC is proposed. Mathematical models for the combined system are established. Performance analysis at designed conditions for the combined system is achieved. Entropy generation rate is calculated to reveal the feasibility and irreversible loss of the system. Top and ambient temperatures are prescribed to reveal the influences on the system performance.